Distal Radius Fracture Treated by Internal Fixation with Plates, Screws and the RALCA® External Mini-fixator - Rafael López Cuellar; Yaniel Truffin Rodríguez; Yudit Pérez Álvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Distal radius fractures are very common in medical practice. In our service, we may not have the most widely used devices for fixation of these fractures at a given moment. For this reason, we must consider all possible combinations within our power to correct them since most of the time, it is impossible to maintain a fracture reduction using a single technique. We present the case of a 24-year-old female patient treated at the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos due to a displaced fracture of the left distal radius caused by impaction. It was successfully stabilized by internal fixation with plates, screws and the RALCA® external mini-fixator.